Perancangan Aplikasi Untuk Menganalisis Penyakit Menggunakan Pengobatan Tanaman Herbal Dan Cara Mengolahnya Dengan Certainty Factor Berbasis Android - A. Yudi Permana (Jurnal SIGMA, 2020)
Applications regarding diseases and herbal plants do not have a diagnostic system that can assist the selection process. Most of the processes used have not used disease analysis / diagnosis. Most of them provide information about diseases or about herbal plants directly. So often users have to look for diseases or plants first to find the information. The method used in designing information systems for diseases and herbal plants is a structured programming method using UML diagrams. When building this application, it takes software such as Apache as a web server, MYSQL as a database, Eclipse. The steps taken are analyzing the needs required by the application, designing according to the needs analysis, building an application program in accordance with the previously made designs, and testing the application. The results of this thesis will present that a disease information system and herbal plants can be developed using Eclipse and MYSQL database. This application that has been built can help the process of analyzing / diagnosing diseases and providing information about what herbal plants can be used as medicine and how to process these plants so that they are really easy for the user to consume. Keyword: Disease and Herbal Plants, Android, Eclipse, Apache